LISE++ Software Updates and Future Plans. Issue 7 (December 2015) - Kuchera, MP; Tarasov, OB; Bazin, D; Sherril, B; Tarasova, KV
Abstract: This paper describes capabilities and future upgrade plans for the isotope production and simulation software that is used at many in-flight fragmentation facilities, namely LISE++. We highlight the process and methods of updating the software while retaining the computational integrity of the code. The calculations of beam transport and isotope production are becoming more computationally intense with the new large scale facilities. Computational improvements as well as the process of updating this large code is discussed.